Spatial-Temporal Accessibility and Inequality of Veterinary Service in Hong Kong: A Geographic Information System-Based Study - Ng, Ka Yiu; Ho, Chun Long; Koh, Keumseok (Frontiers in Veterinary Science, 2022)
Veterinary services are vital to the welfare of pets and their owners. Previous studies examined multiple factors affecting pet owners' decision to consult veterinarians, yet few studied the spatial accessibility of veterinary services. This study is one of the pioneering studies on the spatial-temporal accessibility of veterinary service and how it is associated with social and spatial inequality in Hong Kong. We measured the spatial availability and accessibility of both general and 24/7 veterinary clinics (i.e., veterinary clinics offering service for 24 hours, seven days a week or providing emergency services outside of business hours) using Geographic Information System and principal component analysis. We found that the spatial distribution pattern of general and 24/7 veterinary clinics can be explained by the average district-to-district distances and the area of a district. In addition, social and spatial inequality of access to veterinary services were observed. The spatial accessibility of general veterinary clinics within walking distance is negatively correlated with household size and the number of public-housing and subsidized-housing households, but positively correlated with the number of private-housing households. The spatial availability and accessibility of 24/7 veterinary service are positively correlated with the number of private housing households and households with the highest monthly household income, and the latter also positively correlates with a population with a post-secondary degree, further shedding light on the social and spatial inequality issue that communities with wealthier households and highly educated populations have more accessibility to 24/7 veterinary services. Last, we argue that the need-based veterinary support tends to target remote rural areas while overlooking the new growth areas close to the traditional urban core but poor in accessibility to veterinary care. Therefore, a comprehensive investigation into the pet ownership landscape and their needs over space and time will be beneficial to construct a more robust animal welfare system in Hong Kong.